TRICO - sredstvo za zaščito gozdnega drevja (predvsem mladja) pred objedanjem divjadi - Polajnar, Tomaž (Gozdarski vestnik, 2014)
This article presents the use of TRICO - a new means of protection for forest young growth and compares the protection manner and costs using this new means to the customary Kemakol. Protection of forest trees from game bite represents a high cost for both the owner and the country that subsidizes work and material to the owners. The article presents the good and bad sides of both means of protection and encourages searches for more effective and cheaper means of protection for forest trees from game bite where their use is needed.
Keywords: mlado drevje; zaščita dreves; škoda po divjadi; stroški zaščite; zaščitna sredstva; TRICO; Kranj; izkušnje